[Math] Prove $(A \backslash B)’\backslash (B \backslash A) = B \backslash A$

boolean-algebralogic

Let $A$ and $B$ be subsets of some universal set.
Prove that $(A \backslash B)'\backslash (B \backslash A) = B \backslash A$

Given:

Definition 3.3.1 states that $A$ and $B$ are sets. The complement of $B$ relative to $A$, written $A \backslash B$ is the set
$ A \backslash B =[x:x \in A \land x \notin B]$

Definition 3.3.3 states that $U$ is a universal set and $A \subseteq U$. The complement of $A$, written $A'$ is the set $A' = U \backslash A =[x \in U: x\notin A]$

For B relative to A,

Using Definition 3.3.1

$A \backslash B = [x: x \in A \land x \notin B]$

Using Definition 3.3.3

$(A \backslash B)' = [x : x \in A : x \notin B]$

For A relative to B,

Using Definition 3.3.1

$B \backslash A =[x: x \in B \land x \notin A]$

Using Definition 3.3.3

$(B \backslash A)' = [x: x \in B : x \notin A]$


The $\backslash$ can be read as $-$, so the problem may look like this

$( a-b)' – (b-a) = b-a$

I could try to use one of the Propositionals which is $(B')' = B$

Maybe if B = a – b

$((a-b)')' – (b-a) = b-a$

$(a-b) – (b-a) = b-a$

$(a-b)-b+a = b-a$

$a-b-b+a = b-a$

hmmm that's $2a-2b = b-a$

factoring out the -2 would result in $-2(-a+b) = b-a$

That clearly doesn't equal to b-a.

Is it possible to prove this problem with venn diagrams instead?

I could draw one for $(A \backslash B)'$, $(B \backslash A)$ and $(A \backslash B)' \backslash ( B \backslash A)$

On one diagram, the A would be shaded

On a second diagram, the B would be shaded.

On the third diagram A and B which would be the middle is shaded.

Edit: Maybe a counterexample will work since the left side of the problem could not have the elements of $B \backslash A$, but the right side does.

Or…

since

$(A \backslash B)'\backslash (B \backslash A) = B \backslash A$

applying definitions.
$[x : x \in A : x \notin B]' \backslash [x: x \in B \land x \notin A]$ = $[x: x \in B \land x \notin A]$ ???

Edit: I need to provide an improved version of this proof.

Let $A$ and $B$ be subsets of some universal set.
Prove that $(A \backslash B)'\backslash (B \backslash A) = B \backslash A$

Given:

Definition 3.3.1 states that $A$ and $B$ are sets. The complement of $B$ relative to $A$, written $A \backslash B$ is the set

$ A \backslash B =[x:x \in A \land x \notin B]$

Here is what I have so far…

$( B \backslash A ) = [x: x \in B \land x \notin A]$

that is the end result. I need to somehow work from the left and achieve $(B \backslash A ))$

$(B \backslash A)' =[x:x \notin B \lor x \in A]$

$(A \backslash B)' =[x:x \notin A \lor x \in B]$

I may have to use the definition again, but it is messy.

Set property by default definition is $A \backslash B = A \cap B'$

so from set intersection definition …

$ [x: x \in A \land x \notin B]$

since $(A \backslash B)'$….$ [x: x \notin A \lor x \in B]$

/////

set property $B \backslash A = B \cap A'$

set intersection definition… $[x: x\in B \land x \notin A]$

since $(B \backslash A)'$…$ [x: x\notin B \lor x \in A]$

Edit: Going through the definition is a very bad idea. I've used the set property and was able to get $ B \backslash A$

Best Answer

We think that the statement of the problem is wrong.

As said in the above comments, if we correct it as :

$(A \backslash B)' \backslash (B \backslash A)' = B \backslash A$

we have that the condition for $(A \backslash B)'$ is :

$\lnot (x \in A \land x \notin B)$, that is (using De Morgan) :

$(x \notin A \lor x \in B)$.

With the same approach, the condition for $(B \backslash A)'$ is :

$(x \notin B \lor x \in A)$.

So the "global" condition becomes :

$(x \notin A \lor x \in B) \land \lnot (x \notin B \lor x \in A)$, that is :

$(x \notin A \lor x \in B) \land (x \in B \land x \notin A)$

Now, going back to set properties, this is :

$(A' \cup B) \cap (A' \cap B)$.

But $(A' \cap B)$ is a subset of $(A' \cup B)$, so that their intersection is $(A' \cap B)$.

Now, $x \in (A' \cap B)$ iff $(x \in B \land x \notin A)$ i.e.

$x \in B \backslash A$.